2015
DOI: 10.1080/10643389.2015.1078220
|View full text |Cite
|
Sign up to set email alerts
|

Honey bees and their products: Bioindicators of environmental contamination

Abstract: Human activities produce contaminants, the amounts and toxicity of which often exceed the environment's homeostatic capacity to cleanse itself. Hence, the systematic analysis and monitoring of the environment is increasingly a matter of urgency. Honey bees, thanks to their morphological features, and also bee products are regarded as good indicators of environmental pollution by toxic substances, be these heavy metals, radioactive elements or persistent organic pollutants such as pesticides. The bees can carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(78 citation statements)
references
References 35 publications
1
64
0
7
Order By: Relevance
“…Crane (1984) was the first to propose using apiculture products as biomarkers for environmental contamination. Honeybees can be used to identify chemical disruptions in the environment via two signals: hive death and detection of residues of contaminated substances in apiculture products (Bargańska et al, 2016). A highly notable advantage in using apiculture products as biomarkers is the early and spatial detection of patterns for distinct environmental contaminants (Van Der Steen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Crane (1984) was the first to propose using apiculture products as biomarkers for environmental contamination. Honeybees can be used to identify chemical disruptions in the environment via two signals: hive death and detection of residues of contaminated substances in apiculture products (Bargańska et al, 2016). A highly notable advantage in using apiculture products as biomarkers is the early and spatial detection of patterns for distinct environmental contaminants (Van Der Steen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Turkey ranks second among the other honey producing countries with an annual (2017) production of 114.471 tons (Turkish, 2017;Kaftanoglu, 2017). Botanical and geographical origin of honey is of great importance in terms of its chemical quality (Bargańska et al, 2016;Kılıç Altun et al, 2017). Turkey, owing to its rich plant diversity and favorable climate due to geographical features comes to the forefront in terms of production of high quality honey varieties with high mineral content .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that 75% of the collected 198 honey samples contained at least one insecticide and multiple contaminations were found in 45% of the same batch of samples . The monitoring of pesticide residues in honey and bee products can not only ensure the quality of honey for human consumption, but also serve as an indicator of environmental pollution . Electrospray ionization mass spectrometry (ESI‐MS) is a powerful technique for identification and quantitation of various compounds.…”
Section: Introductionmentioning
confidence: 99%
“…5 The monitoring of pesticide residues in honey and bee products can not only ensure the quality of honey for human consumption, but also serve as an indicator of environmental pollution. [6][7][8] Electrospray ionization mass spectrometry (ESI-MS) is a powerful technique for identification and quantitation of various compounds. Because of its high sensitivity and high accuracy, ESI-MS has been widely used for analysis of pesticide residues in food samples including honey and bee products, [9][10][11] vegetable, 12 fruit juice, 13 and wine.…”
Section: Introductionmentioning
confidence: 99%